Increasing knowledge of the denizens of saline environments through integrative taxonomy: new Argentinian endemic taxa of Liolaemus (Iguania: Liolaemidae) and their evolutionary relationships. Issue 2 (17th November 2020) - Abdala, Cristian S.; Paz, Marcos M.; Semhan, Romina V.; García, Noelia; Aguilar-Kirigin, Alvaro J.; Farías, María E.; Valladares, Pablo; Poblete, Roberto Gutiérrez; Quipildor, Matías A.; Valdes, Julián; Langstroth, Robert
Abstract : The known diversity of the genus Liolaemus continues to increase, principally due to its great degree of endemism, the increasing number of researchers working on it, and advances in the taxonomic and phylogenetic knowledge of the genus. This diversity positions Liolaemus as the second most species-rich tetrapod genus. The present work adds to evidence for the great diversity of Liolaemus through the description of two new species, endemic to saline environments in the Argentinian Puna. Both species are members of the Liolaemus montanus group within the subgenus Eulaemus . To determine the taxonomic status of these lizards, we used integrative taxonomy as a tool, incorporating phylogenetic, morphological, and molecular genetic evidence, as well as the anatomy of hemipenes, statistical morphological analysis, and ecological characteristics. Our analyses supported the conclusion that both sampled populations of lizards are species new to science. One of these is found along the margins of the Antofalla salt flats in the Catamarca Province and the Hombre Muerto salt flats in the Salta Province. The other new species inhabits saline habitats vegetated by Lycium humile, principally between the salt crusts of the Antofalla salt flats. Both species are small to medium sized and can be distinguished from all other species of the L. montanus group by unique combinations of morphological characters, primarily pholidosis and dorsal and ventral colour patterns. urn:lsid:zoobank.org:act:29B39613-3298-4B43-A13A-9F950051BD04 urn:lsid:zoobank.org:act:A97A5AA8-7295-4882-9809-CEFAD72E7202